2004
DOI: 10.1007/s11906-004-0041-5
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and liver disease

Abstract: Arterial hypertension is a common disorder with a frequency of 10% to 15% in subjects in the 40- to 60-year age group. Yet most reports find the prevalence of arterial hypertension in patients with chronic liver disease (cirrhosis) much lower. In this review, we consider the alterations in systemic hemodynamics in cirrhosis. The most characteristic findings in cirrhotic patients are vasodilatation with low systemic vascular resistance, increased cardiac output, high arterial compliance, secondary activation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
10

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 48 publications
1
7
0
10
Order By: Relevance
“…We also observed lower arterial blood pressure and cholesterol levels in the cirrhosis group compared to controls. This is in agreement with previous studies showing an effect of liver cirrhosis on arterial blood pressure and cholesterol [9,10]. Furthermore, we found that malnutrition was common among patients with cirrhosis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We also observed lower arterial blood pressure and cholesterol levels in the cirrhosis group compared to controls. This is in agreement with previous studies showing an effect of liver cirrhosis on arterial blood pressure and cholesterol [9,10]. Furthermore, we found that malnutrition was common among patients with cirrhosis.…”
Section: Discussionsupporting
confidence: 93%
“…The coagulation abnormalities and thrombocytopenia [3,4], as well as the low serum cholesterol [9] and low arterial blood pressure levels [10] frequently seen in cirrhosis, have been proposed as possible protective factors. Diabetes mellitus, a major risk factor of CAD, has been shown, however, to be common in patients with liver cirrhosis [11], but is also reported not to be associated with cardiovascular disease in this group of patients [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The ability to mobilize the gut venous reservoir to defend the circulation when needed is mediated through baroreflexes (26,27). Baroreflex function is known to be impaired in cirrhosis (6,14). But the normalization of this homeostatic response in the cirrhotic rat by a selective nNOS inhibitor indicates that NO plays a role in some aspect of baroreflex regulation of gut venomotor responses.…”
Section: Discussionmentioning
confidence: 99%
“…For example, portal vein ligation normalizes arterial pressure in spontaneously hypertensive rats49; and the onset of portal hypertension in patients with hepatic cirrhosis and essential hypertension also can produce dramatic decreases in arterial pressure50.…”
Section: Vascular Capacitance and Hypertensionmentioning
confidence: 99%